Prediction at the Discourse Level in Spanish–English Bilinguals: An Eye-Tracking Study - Contemori, Carla; Dussias, Paola E. (Frontiers in Psychology, 2019)
In two experiments, we examine English monolinguals’ and Spanish-English bilinguals’ ability to predict an upcoming pronoun referent based on the Implicit Causality (IC) bias of the verb. In an eye-tracking experiment, the monolingual data show anticipation of the upcoming referent for NP1-bias verbs. For bilinguals, the same effect is found, showing that bilinguals are not slower than monolinguals at processing the information associated with the IC of the verb. In an off-line experiment, both groups showed knowledge of IC bias information for the verbs used in the eye-tracking experiment. Based on the findings of the two experiments, we show that highly proficient bilinguals have similar online and off-line predictions based on IC verb information than monolingual speakers.